THE DEVELOPMENTAL PERIOD OF TWO SPECIES OF ANOPHELES MOSQUITOES (DIPTERA: CULICIDAE) FROM THREE VILLAGES AROUND WAD MEDANI TWON - A. Mohamed, Abdalla Ibrahim; Ali A. Kehail, Mutaman (Gezira Journal of Health Sciences, 2009)
This work aimed at studying the developmental periods of the different stages of the vector under laboratory conditions. The study was conducted in three villages around Wad Medani, namely Kereba, Barakat and Hantoub. The research was targeting three species of the vector in all three villages viz. Anopheles arabiensis and A. pharoensis. The tests were conducted in 2001. The oviposition period was longer in A. arabiensis and A. pharoensis (3.0 and 3.2 days, respectively). The oviposition rates were 214.6 and 239.6 eggs/female/day, respectively. Consequently the mean fecundity was higher for those two vector species (762.0 and 760.3 eggs/female). Under laboratory conditions the developmental period of the eggs, larvae, pupae, adult stages and total life cycle for the two species, ranged 2.0-2.5, 5.5 – 6.0, 2.0 – 2.3, 15.5 – 19.5 and 25.0 – 30.0 days, respectively.